La dinámica familiar y su incidencia en el comportamiento de las niñas y niños de preparatoria, primer grado de educación general básica de la escuela Agoyan del cantón Joya de los Sachas, provincia de Orellana. Período lectivo 2013-2014 - Quilligana Luzpa, Marlluri Alexandra (2014)
This thesis refers to "FAMILY DYNAMICS AND ITS IMPACT ON BASIC GENERAL DE EDUCATION FIRST DEGREE CHILDREN BEHAVIOR “AGOYAN” SCHOOL JOYA DE LOS SACHAS CANTON SACHAS, ORELLANA PROVINCE. PERIOD 2013-2014 "conducted according to the provisions of the Regulation of Academic Board It was of Loja National University. The General Objective: Was to analyze the family dynamics in the behavior of girls and boys High School, basic general de education first degree children behavior “Agoyan” school Joya de los Sachas canton Sachas, Orellana province. period 2013-2014. The methods used for the preparation of this research work were : Scientist, Inductive- Deductive , Analytic - Synthetic and Statistical Model, which served them help efficiently achieve the goal. The techniques and instruments used were targeted and applied to parents, First Grade Students to Determine General Education and Family Dynamics Behavioral Test ( Ebee Leon Gross ) Survey applied to children to assess the type of behavior. We conclude that: 100% of parents surveyed believe that there is a real family dynamics is essential the presence of elements such as giving enough love to their children, 89% give a positive treatment, there is a 77 % participatory authority, 74% a while quality of living, and, 64% of intended service in each of the family members. Test results Behavior ( Ebee León Gross) determines that : 54% of children had predominance in response B Assertive behavior, 41% had a predominance in response C Liabilities Behavior, and 5% had a predominance in response equivalent to Aggressive Behavior .